Sharing Economy: Mehr Chancen als Risiken? - Werner Eichhorst; Alexander Spermann (Wirtschaftsdienst, 2016)
Die Sharing Economy ist das Sinnbild für neue, internetbasierte Geschäftsmodelle, die innerhalb weniger Jahre weltweit etabliert werden können. Mit diesen Geschäftsmodellen sind einerseits Hoffnungen auf mehr Wachstum und mehr Beschäftigung und andererseits Sorgen vor unsicheren Beschäftigungsverhältnissen verbunden. Überwiegen die Chancen die Risiken? Sollte der Staat massiv regulieren? – – This article analyses the pros and cons of the new profit-oriented sharing economy. It summarises existing studies on the economic effects of Uber and Airbnb with a special focus on the repercussions for the labor market. It turns out that both business models could lead to additional revenues and employment rather than just crowding-out existing business models. However, unfair competition, exploitation of the self-employed and the destruction of cheap housing seem to be issues. Therefore, the authors conclude that neither laissez-faire nor a ban is the right answer. In order to allow for more growth and employment, appropriate regulation is needed.
Keywords: J2; J8; K2; 330; Share Economy; Geschäftsmodell; Wertschöpfung; Regulierung